The Power of One: Creating the New Culture of Upstanders. (1st October 2016) - Stromsland, Frances C.; Lott-Jones, Jamie; Sok, Mary
Abstract: By infusing social justice themes into social studies lessons and creating interdisciplinary units, educators not only changed the curriculum, but also created a school-wide culture of understanding and valuing human rights .